"Who are these people?" Evaluating the demographic characteristics and political preferences of MTurk survey respondents. (5th September 2015) - Huff, Connor; Tingley, Dustin
As Amazon's Mechanical Turk (MTurk) has surged in popularity throughout political science, scholars have increasingly challenged the external validity of inferences made drawing upon MTurk samples. At workshops and conferences experimental and survey-based researchers hear questions about the demographic characteristics, political preferences, occupation, and geographic location of MTurk respondents. In this paper we answer these questions and present a number of novel results. By introducing a new benchmark comparison for MTurk surveys, the Cooperative Congressional Election Survey, we compare the joint distributions of age, gender, and race among MTurk respondents within the United States. In addition, we compare political, occupational, and geographical information about respondents from MTurk and CCES. Throughout the paper we show several ways that political scientists can use the strengths of MTurk to attract respondents with specific characteristics of interest to best answer their substantive research questions.